A time for self-care? Frontline health workers' strategies for managing mental health during the COVID-19 pandemic - Sophie Lewis; Karen Willis; Marie Bismark; Natasha Smallwood (Elsevier, 2022)
Frontline healthcare workers have experienced detrimental mental health impacts during the COVID-19 pandemic including anxiety, emotional distress, stress, fatigue, and burnout. But little is known about how these healthcare professionals take care of their own mental health in the midst of considerable personal, occupational and social disruption. In this article, we use qualitative data from an Australian national survey to examine the self-care strategies frontline healthcare professionals employed to manage their mental health and wellbeing during the crisis. Findings reveal how healthcare workers sought to adjust to disruption by adopting new self-care practices and mindsets, while encountering numerous personal and professional struggles that undermined their capacity for self-care. Feeling socially connected and valued were critical dimensions of caring for self, illustrating the importance of locating self-care in the social domain. These findings, we argue, highlight the need to expand conceptions of self-care away from those that focus primarily on the individual towards approaches that situate self care as collective and relational.